Damping behavior of fibrous composites with viscous interface under longitudinal shear loads - He, L.H.; Liu, Y.L.
Mechanical damping of fiber composites with viscous interface under longitudinal shear loads is analyzed. The specific damping capability is obtained explicitly by using the micromechanical model of composite cylinders assemble. The study indicates that the effective damping of the composite depends on several factors, including fiber volume fraction, the relative shear rigidity of fiber to matrix, and a dimensionless parameter composed of interface viscosity, fiber radius, vibration frequency and shear modulus of matrix. The respective influences of these factors are discussed in detail, and the results are expected helpful in tailoring microstructure of composites with desired damping behaviors.
Keywords: B. MODELING; B. INTERFACE; C. ANELASTICITY; C. COMPLEX MODULI